ENHANCING THE PRONUNCIATION OF ENGLISH SUPRASEGMENTAL FEATURES THROUGH REFLECTIVE LEARNING METHOD - Suwartono, Suwartono; Rafli, Zainal (PPs UNJ, 2015)
Suprasegmentals are of paramount importance in spoken English. Yet, these pronunciation features are marginalised in EFL/ESL teaching-learning. This article deals with a study through reflective learning method andÂ That aims to describe the increase in supramental english skill find out if the improvements achieved in the english pronounciation. Kemmis and Taggartâs model of action research was adopted. The study involved twenty-four undergraduate students at Muhammadiyah University of Purwokerto, Indonesia. The investigation contained two cycles, each of which comprised three sessions. Data were gathered through observation, recorded conversation, diary, interview, and test. Overall, the study has shown that reflective method using video integrated into communicative activities enhanced student involvement in learning the pronunciation of English suprasegmentals. Students got involved in monitoring and evaluating their own learning. In addition, a majority of the students gave positive response to the instruction. Level of pronunciation mastery rose sharply from only 4.16% of students passing the test in the pre-intervention (baseline) to 65.21% in first cycle, and 73.9% in second cycle. Most studentsâ pronunciation to some degree sounded âmore Englishâ.